1991
DOI: 10.1007/bf02536434
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism inTaphrina deformans treated with sterol biosynthesis inhibitors

Abstract: Changes in the unsaturated fatty acid content of the fungusTaphrina deformans as a function of growth, temperature, and sterol content were investigated. It was found that the highest growth rate was accompanied by a relatively high degree of fatty acid unsaturation (18∶1<18∶2+18∶3) and low sterol (brassicasterol) content. Also, a substantial shift in the degree of unsaturation from mainly 18∶2+18∶3 to 18∶1 occurred in the later stages (mid‐linear) of culture development. Cells readily adapted from 18°C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Similar changes in plasma membrane CLB fatty acids have been reported in U. maydis in response to triarimol (an azole antifungal; Ragsdale, 1975), in Candida albicans treated with 0.1 pM ketoconazole (Vanden Bossche, 1993) and in 7'. deformans treated with propiconazole (Weete et al, 1985(Weete et al, , 1991. Surprisingly, in the present study, normal sterol depletion was not the primary cause for these changes.…”
Section: Fatty Acidscontrasting
confidence: 55%
See 1 more Smart Citation
“…Similar changes in plasma membrane CLB fatty acids have been reported in U. maydis in response to triarimol (an azole antifungal; Ragsdale, 1975), in Candida albicans treated with 0.1 pM ketoconazole (Vanden Bossche, 1993) and in 7'. deformans treated with propiconazole (Weete et al, 1985(Weete et al, , 1991. Surprisingly, in the present study, normal sterol depletion was not the primary cause for these changes.…”
Section: Fatty Acidscontrasting
confidence: 55%
“…Also, work on 7'. deformans suggested that fungicide-induced fatty acid unsaturation was not dependent on abnormal sterol accumulation, although it could not be correlated with growth rate (Weete et al, 1991). Therefore, in the context of the present work, the changes in linoleic to oleic acid ratio can be better understood as a stress response rather than a direct consequence of the presence of non-functional sterols.…”
Section: Fatty Acidsmentioning
confidence: 64%
“…These results are different from the reported effects of other antifungal agents, especially those inhibiting ergosterol biosynthesis. For example, in Candida albicans , a pronounced shift from monounsaturated to diunsaturated fatty acids and, after prolonged treatment, from oleic to palmitic acid was observed with miconazole and ketoconazole [2] and also with other antifungal agents inhibiting either sterol 14‐demethylation or squalene epoxidation [3–5]. A shift from oleic to linoleic acid was observed in the non‐esterified fatty acid fraction of U. maydis treated with triarimol [1].…”
Section: Resultsmentioning
confidence: 99%
“…For example, inhibition of ergosterol biosynthesis by azoles is well established and is accepted as their primary mechanism of action [1, 2]. Besides inhibiting ergosterol biosynthesis, these antifungal agents often also alter the pattern of fatty‐acyl chains in membrane lipids, mainly phospholipids, and, in some cases, increase the amounts of non‐esterified fatty acids [1–5]. The nature of these effects has not been explained unambiguously and several hypotheses have been proposed to explain them: the changes may reflect a non‐specific slowing‐down of culture growth [4]; they may be compensatory, in order to alleviate alterations in membrane lipid fluidity or phase; or they may be the result of direct effects on fatty acid metabolizing enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo effect of CLB‐fatty acids on H + ‐ATPase activity, particularly under stress, had been suggested previously [17], but lack of an appropriate experimental system probably prevented its demonstration. In our system, the modification of the fatty acid moieties was provoked by the presence of abnormal sterols plus, in the case of EBI‐treated sporidia, other collateral effects of these compounds [33]. In U. maydis , changes in the plasma membrane 18 : 2/18 : 1 ratio followed the inhibition of growth rate, which was influenced not only by the biosynthetic point affected but also by the method used [21].…”
Section: Discussionmentioning
confidence: 99%